A novel strategy for optimal component formula of anti-PRRSV from natural compounds using tandem mass tag labeled proteomic analyses - Hua Zhang; Zhigang Cao; Panpan Sun; Ajab Khan; Jianhua Guo; Yaogui Sun; Xiuju Yu; Kuohai Fan; Wei Yin; E Li; Na Sun; Hongquan Li (BMC Veterinary Research, 2022)
Abstract Background Porcine Reproductive and Respiratory Syndrome (PRRS) is one of the most important porcine viral diseases which have been threatening the pig industry in China. At present, most commercial vaccines fail to provide complete protection because of highly genetic diversity of PRRSV strains. This study aimed to optimize a component formula from traditional Chinese medicine(TCM)compounds with defined chemical characteristics and clear mechanism of action against PRRSV. Methods A total of 13 natural compounds were screened for the anti-PRRSV activity using porcine alveolar macrophages (PAMs). Three compounds with strong anti-PRRSV activity were selected to identify their potential protein targets by proteomic analysis. The optimal compound formula was determined by orthogonal design based on the results of proteomics. MTT assay was used to determine the maximum non-cytotoxic concentration (MNTC) of each compound using PAMs. QPCR and western blot were used to investigate the PRRSV N gene and protein expression, respectively. The Tandem Mass Tag (TMT) technique of relative quantitative proteomics was used to detect the differential protein expression of PAMs treated with PRRSV, matrine (MT), glycyrrhizic acid (GA) and tea saponin (TS), respectively. The three concentrations of these compounds with anti-PRRSV activity were used for orthogonal design. Four formulas with high safety were screened by MTT assay and their anti-PRRSV effects were evaluated. Results MT, GA and TS inhibited PRRSV replication in a dose-dependent manner. CCL8, IFIT3, IFIH1 and ISG15 were the top four proteins in expression level change in cells treated with MT, GA or TS. The relative expression of IFIT3, IFIH1, ISG15 and IFN-β mRNAs were consistent with the results of proteomics. The component formula (0.4 mg/mL MT + 0.25 mg/mL GA + 1.95 μg/mL TS) showed synergistic anti-PRRSV effect. Conclusions The component formula possessed anti-PRRSV activity in vitro, in which the optimal dosage on PAMs was 0.4 mg/mL MT + 0.25 mg/mL GA + 1.95 μg/mL TS. Compatibility of the formula was superposition of the same target with GA and TS, while different targets of MT. IFN-β may be one of the targets of the component formula possessed anti-PRRSV activity.